2019
DOI: 10.1136/vr.105082
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in morbidity and mortality of dairy calves from an injectable trace mineral supplement

Abstract: The effect of a multimineral preparation on the health and growth of spring born, dairy calves was investigated on four New Zealand pastoral farms. Calves were randomly allocated injections within 24 hours of birth, 35 days and 70 days after birth. Injections contained 40 mg zinc, 10 mg manganese, 5 mg selenium, 15 mg copper and 5 mg chromium per ml (Multimin+Se+ Cu+Cr Cattle, Virbac South Africa) at 1 ml/50 kg body weight. Morbidity, mortality from natural challenge and growth rates were recorded for 140 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 36 publications
3
7
1
Order By: Relevance
“…Few studies are present in the international literature about ewe colostrum composition, and little is known about the colostrum mineral concentrations in different dairy breeds. Moreover, there is growing evidence of the involvement of minerals on the immune and antioxidant responses that are key for preserving newborns’ health, and there is interest in trace mineral supplementation to maximize these positive effects in calves [ 50 ]. To understand the relationships and the correlations between the minerals and other constituents of colostrum will allow for a targeted intervention in the mineral integration of young ruminants.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies are present in the international literature about ewe colostrum composition, and little is known about the colostrum mineral concentrations in different dairy breeds. Moreover, there is growing evidence of the involvement of minerals on the immune and antioxidant responses that are key for preserving newborns’ health, and there is interest in trace mineral supplementation to maximize these positive effects in calves [ 50 ]. To understand the relationships and the correlations between the minerals and other constituents of colostrum will allow for a targeted intervention in the mineral integration of young ruminants.…”
Section: Discussionmentioning
confidence: 99%
“…An increase of the immunoglobulin concentration in calves has been demonstrated to be caused by a mineral selenium supplementation of cows before calving [39,43]. Many reports have already substantiated the importance of optimal calf mineral status in improving immune function during the first months of life [29,[44][45][46]. In addition, other researchers have demonstrated that supplemental injections of Zn, Mn, Cu, and Se, increased humoral and cellular immune response and glutathione peroxidase activity in dairy calves [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…Injectable trace mineral (ITM) supplements combining several trace minerals, such as Se, Cu, Zn, and Mn, have recently become available on the market, allowing rapid availability and transport of trace minerals in the blood after injection [11]. Bates and others showed that ITM supplements reduce morbidity and mortality of dairy calves from birth to 140 days [29]. However, to the authors' best knowledge, there are no equivalent data for newborn and pre-weaned beef calves.…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that milk composition varies across breeds (Cerbulis and Farrell, 1976;Auldist et al, 2004;Carroll et al, 2006), but little is known about the colostrum mineral concentrations and total yields in breeds other than Holstein. There is growing evidence of the involvement of minerals on immune and antioxidant responses key to preserve calf health, and there is interest on trace mineral supplementation to maximize these positive effects in calves (Teixeira et al, 2014;Kertz et al, 2017;Bates et al, 2019). Thus, although mineral requirements of neonate calves are not clearly defined, further description and understanding of factors influencing colostrum mineral concentrations are warranted to allow for an optimum use of this supply.…”
Section: Introductionmentioning
confidence: 99%